Patient-centred consent in women's health: does it really work in antenatal and intra-partum care? - Jacqueline Nicholls; Anna L David; Joseph Iskaros; Anne Lanceley (BMC, 2022)
Abstract Background Legal and social changes mean that information sharing and consent in antenatal and intrapartum settings is contentious, poorly understood and uncertain for healthcare professionals. This study aimed to investigate healthcare professionals' views and experiences of the consent process in antenatal and intrapartum care. Methods Qualitative research performed in a large urban teaching hospital in London. Fifteen healthcare professionals (obstetricians and midwives) participated in semi-structured in-depth interviews. Data were collectively analysed to identify themes in the experiences of the consent process. Results Three themes were identified: (1) Shared decision-making and shared responsibility -engaging women in dialogue is often difficult and, even when achieved, women are not always able or do not wish to share responsibility for decisions (2) Second-guessing women - assessing what is important to a woman is inherently difficult so healthcare professionals sometimes feel forced to anticipate a woman's views (3) Challenging professional contexts - healthcare professionals are disquieted by consent practice in the Labour ward setting which is often at odds with legal and professional guidance. Conclusions Results suggest that there is a mismatch between what is required of healthcare professionals to effect an antenatal or intrapartum consent process concordant with current legal and professional guidance and what can be achieved in practice. If consent, as currently articulated, is to remain the barometer for current practice, healthcare professionals need more support in ways of enabling women to make decisions which healthcare professionals feel confident are autonomous whatever the circumstances of the consultation.